Etyka w społecznej gospodarce rynkowej - Przybyciński, Tomasz (Annales. Etyka w Życiu Gospodarczym, 2008)
Respecting the rights of man, the social market economy is aimed at maintaining a high rate ofeconomic growth, price stability, full employment, healthy competition, good working conditionsand public services. That is just why the social market economy is not far removed from the objectivedemands of the moral order, from the exigencies of justice and social love.